Spectacle, Oppression, and Resistance: Class Struggle in Gladiator II through Marxist Criticism - Kusen, Felicia Jessica; Tatemba, Filmorevo Jesse Lincoln; Lie, Jesslyn Quaneisha; Martin, Dominic Thomas; Tambunan, Aubrey Jemima; Sabuin, Kezia Jade Meizie (Jurnal Pendidikan Makarios, 2025)
This article examines Gladiator II (2024) through the lens of Karl Marx’s theory of class struggle. Using textual and thematic analysis, the study explores how the film portrays structural inequality, labor exploitation, and the emergence of resistance within ancient Roman society. The findings indicate three key results: 1) the depiction of slavery and gladiatorial combat embodies Marx’s concept of commodification of labor, revealing the economic foundations of Roman spectacle. 2), the transformation of Lucius Verus illustrates the development of class consciousness, shifting from individual survival to collective solidarity. 3), the film’s portrayal of Rome’s decline demonstrates historical materialism, showing how contradictions in production and power relations lead to social revolution. These insights position Gladiator II not merely as entertainment but as a cultural text that critiques systemic oppression and mirrors contemporary issues such as inequality, corruption, and political dominance. By employing Marxist criticism, the study affirms the relevance of class struggle as both a historical and modern narrative.